2014 International Conference on Control, Instrumentation, Communication and Computational Technologies (ICCICCT) 2014
DOI: 10.1109/iccicct.2014.6993145
|View full text |Cite
|
Sign up to set email alerts
|

Validation of requirement elicitation framework using finite state machine

Abstract: Requirement elicitation is considered to be a very vital activity in requirement engineering. It is a proven fact that improper elicitation of requirements leads to a project failure. S o for the improvement in the software industry's success rate more attention is required in the elicitation process. In order to help elicitor to understand and select different methods, many frameworks are proposed that highlight the key issues of requirement elicitation but most of the frameworks are theoretical in nature. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…The group techniques are important in eliciting requirements because software engineering is a group activity [31] [32]. In [33] suggests that one to one interview is the most suitable method for requirement gathering. In [34] researchers suggest that workshop is most suitable technique for small scale software projects whereas [35] suggest that DSDM is suitable for large scale software projects.…”
Section: Related Workmentioning
confidence: 99%
“…The group techniques are important in eliciting requirements because software engineering is a group activity [31] [32]. In [33] suggests that one to one interview is the most suitable method for requirement gathering. In [34] researchers suggest that workshop is most suitable technique for small scale software projects whereas [35] suggest that DSDM is suitable for large scale software projects.…”
Section: Related Workmentioning
confidence: 99%
“…In [7], a framework is proposed for obtaining requirements that support the requirements engineer in understanding and selecting methods for obtaining requirements, where techniques selection for eliciting requirements is addressed. This article proposes a selection approach of requirements elicitation techniques based on neural networks, considering key attributes related to the problem domain and the sources of the requirements.…”
Section: Related Workmentioning
confidence: 99%
“…Requirements engineering is a key stage for the success of a software system [6]. In fact, it is revealed that, of the total of failed projects, 50% of them failed at the requirements engineering stage [7]. A poor requirements elicitation is the cause of up to 71% of failures in software projects [8], and it is responsible for up to 70% of the errors of the final systems [7].…”
Section: Introductionmentioning
confidence: 99%
“…El proceso de elicitación de requerimientos es la primera etapa de la ingeniería de requisitos donde se abstrae la comprensión del problema que se desea resolver con el producto de software, buscando así determinar y documentar los requisitos; constituye un proceso complejo en el que se presentan no solo problemas esenciales, sino accidentales [1], entre los que se pueden mencionar problemas de alcance, comprensión y volatilidad. La elicitación de requerimientos permite a los integrantes de un equipo de trabajo comprender los aspectos particulares del software, a fin de asegurar que su desarrollo posterior guarde relación y coherencia con las especificaciones iniciales del proyecto [2]. Existen muchas alternativas para la elicitación de requerimientos, sin embargo, algunas toman en cuenta el contexto en el que se envuelve el sistema y otras toman en cuenta el origen de los requerimientos; así, es importante por tanto proponer un framework [3] que permita recoger lo mejor de los enfoques de metodologías ágiles y tradicionales, adaptado a sistemas que consumen servicios.…”
Section: Introductionunclassified